Pilot for Harmonization of Diagnostic Protocols for Tomato Brown Rugose Fruit Virus (ToBRFV) in Tomato and Pepper Seeds - Vessela Mavrodieva; Geoffrey Dennis; Beatriz Xoconostle-Cázares; Kevin Ong; Brooke Zale; Jennifer Nickerson; Edward Podleckis; Angel Ramírez-Suárez; Marlene Ortíz-Berrocal; Alonso Suazo; Stephanie Bloem (PhytoFrontiers)
Global seed trade is subject to various national, regional, and international regulations to prevent the introduction and spread of harmful seed-borne and seed-transmitted pathogens. When the plant health regulatory agencies of trading partners employ different diagnostic protocols for the same pathogen, contradictory test results may require additional testing that can cause delays in trade. Establishing equivalency of diagnostic protocols may expedite trade by adding confidence to diagnostic test results. The member countries of the North American Plant Protection Organization (NAPPO) conducted a project evaluating several diagnostic protocols for a seed-transmitted virus, tomato brown rugose fruit virus (ToBRFV), an emerging pathogen that has severely affected tomato and pepper fruit and seed production and trade globally. The objective of the study was to find protocols that could be harmonized among NAPPO member countries, thereby avoiding retesting of samples at different border points. The project was a collaboration between academia, industry, trade organizations, and national plant protection organizations (NPPOs). Three end-point PCR and two real-time PCR protocols were evaluated via a ring test. Nine laboratories from Canada, the United States, and Mexico participated in the ring test, which generated 3,680 data points from analytical, diagnostic, and calibrator samples. Four out of five diagnostic protocols were found to be fully transferable, and three protocols demonstrated optimal performance for accurate, reproducible, and user-friendly detection. The results of this regional effort will simplify the detection of ToBRFV-infected seeds in NAPPO member countries and demonstrate a way to establish equivalency of testing methods between the NPPOs. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.